Routine and preventive health care use in the community among women sentenced to probation - Jennifer Lorvick; Jordana L. Hemberg; Erica N. Browne; Megan L. Comfort (BMC, 2022)
Abstract Background Women involved in the criminal legal (CL) system in the United States have much higher levels of chronic and infectious illness than women in the general population. Over 80% of women in the CL system are on community supervision, which means they receive health care in community settings. While the use of Emergency Department care among CL involved populations has been examined fairly extensively, less is known about engagement in routine and preventive medical care among people on community supervision. Methods We conducted a longitudinal study of health care utilization among women with Medicaid who were currently or previously sentenced to probation in Alameda County, CA (N = 328). At baseline, 6- and 12-months, we interviewed participants about every medical care visit in the six months prior, and about potential influences on  health care utilization based on the Behavioral Model for Vulnerable Populations (BMVP). Associations between BMVP factors and utilization of routine or preventive care were estimated using Poisson regression models with robust standard errors. Generalized estimating equations (GEE) were used account for repeated measures over time. Results A diagnosis of one or more chronic illnesses was reported by 82% of participants. Two-thirds (62%) of women engaged in routine or preventive care in the six months prior to interview. A quarter of women engaging in routine or preventive care did not have a primary care provider (PCP). Having a PCP doubled the likelihood of using routine or preventive care (adjusted Relative Risk [adjRR] 2.27, p < 0.001). Subsistence difficulty (adjRR 0.74, p = 0.01) and unmet mental health care need (adjRR 0.83, p = 0.001) were associated with a lower likelihood of using routine or preventive care. Conclusion Findings underscore the importance of meeting the basic needs of women on community supervision and of connecting them with primary health care providers.